Peranan Pemberian Kuning Telur Dengan Dosis Pengenceran Yang Berbeda Terhadap Tingkat Kelangsungan Hidup Benih Ikan Mas - Agustini, Maria (Techno-Fish, 2017)
Abstract :This research concerning dose thinning of different egg yolk to goldfish seed . To obtain;get dose thinning of best egg yolk as initial feed to storey of continuity of goldfish seed life. Research result indicate that storey continuity of different life, with storey continuity of highest life is treatment of C 60,36 % followed treatment of D 56,5 % treatment of B 52,62%%,, treatment of A 48,9 % and low treatment is treatment of E that is 45,56 %.Â Keyword : egg yolk, Goldfish seed, continuity of life